Women's Leadership Development Programs - Shatrela Washington-Hubbard (Adult Education Research Conference, 2016)
Women continue to hold low percentages of leadership positions in several industries. Although women may seek leadership opportunities, women still face workforce barriers that their male counterparts do not encounter. This discussion will focus on the need for leadership development programs designed specifically for women in order to improve the percentages of women in leadership positions.
Keywords: Career development; Leadership development; Women